Longbourn [compact disc, unabridged] - Baker, Jo (Random House Audio : Books on Tape, 2013)
The servants at Longbourn estate, only glancingly mentioned in Jane Austen's classic, take center stage in Jo Baker's new novel. Here are the Bennets as we have never known them, seen through the eyes of those scrubbing the floors, cooking the meals, emptying the chamber pots. Our heroine is Sarah, an orphaned housemaid beginning to chafe against the boundaries of her class. When the militia marches into town, a new footman arrives under mysterious circumstances, and Sarah finds herself the object of the attentions of an ambitious young former slave working at neighboring Netherfield Hall, the carefully choreographed world downstairs at Longbourn threatens to be completely, perhaps irrevocably, up-ended. From the stern (but soft-hearted housekeeper) to the starry-eyed kitchen maid, these new characters come to life.